Jesus & the rise of early Christianity : a history of New Testament times - Barnett, Paul (Paul William) (Downers Grove, Illinois InterVarsity Press, 1999)
"In Jesus & the Rise of Early Christianity Paul Barnett not only places the New Testament within that world of caesars and Herods, proconsuls and Pharisees, Sadducees and revolutionaries, but argues that the mainspring and driving force of early Christian history is the historical Jesus. We cannot understand the rise of Christianity apart from this Jesus, the Messiah of Israel, and the spiritual and intellectual impact he had on his immediate followers and those who succeeded them." "Jesus & the Rise of Early Christianity is a comprehensive survey of New Testament history that will meet the needs of students and teachers of the New Testament. In its engagement with contemporary scholarship and its emphasis on the propelling role of the historical and risen Jesus in the rise of Christianity, it provides a timely rejoinder to current revisionism in the exploration of Christian origins."--Jacket.
The New Testament as history -- The impact of Christ -- The Hellenistic background to Jesus -- Herod, Idumaean, King of the Jews -- Jesus' birth & boyhood -- Jesus' context: Galilee & Peraea -- Jesus' context: Judea -- Jesus of Nazareth (c. 29-33) -- Resurrection, exaltation & the Spirit -- The community of the Messiah in Jerusalem (c. 33/34) -- The scattering of the community & the conversion of Saul (c.34/35) -- Peter in Palestine (33-47) -- The apostolate of Saul in the "unknown years" (c.34-47) -- The inclusion of the Gentiles (47-49) -- James, Cephas & John -- Paul's later ministry (c. 50-65) -- Churches & evangelists (33-100) -- The four Gospels -- The kingdom of Christ.
Includes bibliographical references (pages 423-429) and indexes.
WJC Memorial to Marjorie Kilker.
Keywords: Bible. -- History of Biblical events; Bible. -- History of contemporary events; Church history -- Primitive and early church, ca. 30-600.